2021
DOI: 10.1371/journal.pone.0250216
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata is not a risk factor for heart diseases: A 10-year retrospective cohort study

Abstract: Alopecia areata (AA) is an autoimmune skin disease caused by chronic inflammation of hair follicles. Chronic inflammatory skin diseases such as psoriasis and lupus erythematosus can increase the risk of cardiovascular diseases. However, the relationship between AA and heart diseases (HDs) remains unclear. Therefore, we conducted this retrospective cohort study to evaluate the risk of subsequent HDs in patients with AA. We reviewed 3770 cases of AA and from 18,850 age, sex, and income level-matched controls fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…No increase [27,62,63] Increased; IR 0.93-0.99/100 PY [64,65] Risk of VTE Increased; IR of 0.33-0.79/100 PY [66][67][68][69][70][71][72][73][74] Possibly increased [75][76][77]; o IR 0.18-0.24/ 100 PY [76,77] No increase; IR 0.09/100 PY [77] Increased; IR 0.52-1.85/100 PY [74,[78][79][80] Risk of malignancy Increased [81][82][83]; by 10% overall versus general population [81] (lymphoma SIR 2.46, lung SIR 1.64, melanoma SIR 1.3) [81] Reduced for colorectal cancer (SIR 0.77) [81] and some hormone-dependent cancers No increase, except lymphoma [33,51] p Uncertain [84][85][86] Increased, SIR of 1.14 overall, including lymphoma [87,88] Table 1 Definition of obesity varied across studies [33] e Depending on the definition of hypertension [33] f Depending on the definition of CVD: includes coronary artery disease, myocardial infarction, congestive heart failure, stroke, peripheral vascular disease [33] g…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No increase [27,62,63] Increased; IR 0.93-0.99/100 PY [64,65] Risk of VTE Increased; IR of 0.33-0.79/100 PY [66][67][68][69][70][71][72][73][74] Possibly increased [75][76][77]; o IR 0.18-0.24/ 100 PY [76,77] No increase; IR 0.09/100 PY [77] Increased; IR 0.52-1.85/100 PY [74,[78][79][80] Risk of malignancy Increased [81][82][83]; by 10% overall versus general population [81] (lymphoma SIR 2.46, lung SIR 1.64, melanoma SIR 1.3) [81] Reduced for colorectal cancer (SIR 0.77) [81] and some hormone-dependent cancers No increase, except lymphoma [33,51] p Uncertain [84][85][86] Increased, SIR of 1.14 overall, including lymphoma [87,88] Table 1 Definition of obesity varied across studies [33] e Depending on the definition of hypertension [33] f Depending on the definition of CVD: includes coronary artery disease, myocardial infarction, congestive heart failure, stroke, peripheral vascular disease [33] g…”
Section: Methodsmentioning
confidence: 99%
“…The risk of heart disease (heart failure, angina pectoris, acute or chronic MI) does not appear to be increased in patients with AA [ 62 ], although conflicting findings reporting small increases or decreases in risk have been reported (Fig. 1 ; Table 1 ).…”
Section: Adverse Events Of Special Interest: Baricitinib Clinical Evi...mentioning
confidence: 99%
“…All registered and claimed data of the sampled individuals constituted the longitudinal database. The validity and usefulness of the cohort data have been verified in previous studies ( 15 19 ).…”
Section: Methodsmentioning
confidence: 52%
“…A study performed by Kang et al [13] revealed higher incidence rates of stroke during a 3-year follow up period in patients with alopecia areata compared to controls (5.44 vs. 2.75 per 1000 person per year). On the contrary, a 10-year retrospective cohort study by Lee et al [14], which included 3770 patients with alopecia areata and 18,850 controls, revealed no significant differences in the incidence of various cardiovascular diseases between those two groups. Heart failure was reported in 0.3% of patients with alopecia areata and in 0.2% of the healthy controls.…”
Section: Discussionmentioning
confidence: 89%